Strategi Pemolisian Pencegahan Kejahatan Penipuan Melalui Media Elektronik di Polres Metro Jakarta Pusat - Tiksnarto Andaru Rahutomo* (Airlangga Development Journal, 2019)
This research is intended to explore the strategy of policing in the prevention of fraud crime through  lectronic media. The focus of this paper is to provide an in-depth overview of the characteristics of fraud crimes through electronic media, factors that contribute to the implementation of policing strategies in preventing these crimes at the Central Jakarta Metro Police, as well as an ideal policing strategy in preventing these crimes. The theoretical perspective that will be used in this research is police science, especially to the perspective of preventive policing strategies as described in a simultaneous strategy for social problems. Based on the background of the phenomenon above, in order to realize public security and order, the author feels the need to develop various crime prevention approaches or strategies that use a combination of various forms of the above mentioned strategies. Therefore, the author feels interested in discussing the problem of policing the prevention of fraud crime through electronic media at the Central Jakarta Metro Police.